Big Five personality and mind wandering in athletes: mediating role of trait anxiety - Li, Yueming; Ma, Jifei; Xi, Yue; Li, Jieling (Frontiers in Psychology, 2024)
Objective Mind wandering is a common phenomenon among athletes during training and competition, and can lead to poor performance. We attempt to clarify which personality type is more prone to mind wandering and the role of trait anxiety between them. Methods Six hundred and eighty-one athletes participated in this cross sectional study. Participants completed the Athlete Mind Wandering Scale, The Chinese adjectives scale of Big-Five factor personality short scale version and Pre-Competition Emotion Scale-Trait questionnaires. The survey data was tested for common method biases, Pearson correlation analysis, and structural equation model by SPSS 25.0 and Mplus 7.0. Results Common method biases can be accepted in this study. (1) Athletes' neuroticism was significantly and positively correlated with trait anxiety and mind wandering, respectively, athletes' extraversion, agreeableness, conscientiousness, and openness were significantly and negatively correlated with trait anxiety and mind wandering respectively; the athletes' trait anxiety was significantly and positively correlated with mind wandering; (2) By constructing mediating models, the direct effects of athletes' extraversion, agreeableness, conscientiousness, neuroticism, and openness on mind wandering were insignificant. The mediating effect of athletes' trait anxiety between the five personalities and mind wandering was significant. Conclusion Trait anxiety in athletes plays a fully mediating role between the relationship of personality and mind wandering. Athletes' extraversion, agreeableness, conscientiousness, neuroticism, and openness can all have an impact on mind wandering through the mediating role of trait anxiety. Athletes can use the mediating role of trait anxiety to intervene the frequency of mind wandering.